(untitled) (Revista Argentina de Musicología, 2018)
Luis Milici’s Symphony ´In Memoriam´ written as an homage to María Eva Duarte, was premiered at the Teatro Municipal of Santa Fe on August 21, 1954, two years after her death. The work had been awarded the first prize in a competition for pieces honoring her memory organized by the Universidad Nacional del Litoral in 1953. The titles of its five movements stem from Peronism’s own vocabulary and indicate the political and personal trajectories of Eva Perón: “The Advent,” “The Poor, “The Privileged,” “The Joyful People,” “The Passing to Immortality.” Milici himself wrote a “programme” for the piece, explaining in detail the intention and meaning of each movement. Composed for symphonic orchestra, solo vocal quartet, mixed choir, children’s choir, and a small guitar ensemble, this symphony constitutes a veritable inventory of ideologemes that Peronism had manufactured to construct its symbolic apparatus. In order to transpose the ideologemes into artistic forms, the composer employs rhetorical devices or musical topoi of representation. Here, a number of ideologemes central to Peronist thought appear, articulated by music. Among them we find the palingenetic idea of a New Argentina that transformed the dramatic past into a luminous present, as well as the idea of Peronism as a secular and political religion.